THE EFFECT OF PLAYABILITY ON USER EXPERIENCE IN "JOKO RUN" GAME - Marisha Pertiwi; Riwinoto , S.T., M.Kom.; Ilmi Nazar Hamdi; Wenny Febrina Putri (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2019)
Playability is the easiness of a game player in playing games, while user experience is a game player's reference to the level of satisfaction of a game. A game certainly has an element of playability so that connoisseurs always play the game so as to produce a high level of user experience. Joko Run is one of the games similar to Subway Surfer game which is the best endless runner game for android that is easy to play. The purpose of this study is to find out the aspects of playability and user experience that must be fulfilled by game developers when designing a game and the influence of playability of the game on the level of user experience of the game "Joko Run". This study uses descriptive and verification methods, descriptive methods to know the aspects of playability and user experience, then the verification method to find the influence of playability on the user experience. Based on the results of the descriptive analysis of playability obtained an average of 109.05, in the range of 105-129, which is easy. Whereas for descriptive analysis user experience obtained an average of 110.25, which is in the scale of 105-129, which is easy. Based on the results of the verification analysis obtained the coefficient of determination or the influence of playability on the user experience of 0.664 or 66.4%, is between 0.60-0.799 which is strong. So, game players can play "Joko Run" easily without having to learn the pattern of the game. Game players can also use the game features "Joko Run" smoothly, so that users feel the ease of playing the game and enhance the experience of the game player "Joko Run. Then, there is the influence of playability on the user experience game "Joko Run". A game that has easy playability tends to increase user experience, on the contrary if the playability of a game is low then it decreases the user experience.